Prevalence of gastro-intestinal parasites of backyard chickens (Gallus domesticus) in and around Shimoga - Javaregowda, Ananda K. (J Parasit Dis, 2014)
The present study was conducted for 1 year from March 2010 to February 2011 to identify gastro-intestinal parasites of backyard chickens and to estimate its prevalence in and around Shimoga, a malnad region of Karnataka. A total of 250 gastro-intestinal tracts were collected from backyard chickens for the detection of gastrointestinal parasites. Among the 250 birds screened, 183 (73.2 %) were found positive for gastrointestinal parasites by gross examination of gastrointestinal tract. Out of 183 positive cases, 94 (51.36 %) were found positive for cestodes, includes 73 (77.6 %) Raillietina tetragona, 12 (12.8 %) Raillietina echinobothrida and 9 (9.6 %) Raillietina cesticillus. Whereas, 53 (28.96 %) were found harbouring nematode parasites includes 33 (62.3 %) had Ascaridia galli, 12 (22.6 %) had Heterakis gallinarum and 8 (15.1 %) had both A. galli and H. gallinarum infection. The remaining 36 (19.67 %) had mixed infections of both cestode and nematode parasites. The microscopic examination of the gut contents and faecal samples showed presence of coccidian oocysts and eggs of A. galli, H. gallinarum and Capillaria spp. respectively.